A study on clinico- laboratory parameters of children with scrub typhus in Garhwal region of Himalayan belt - Dr. Vyas Rathore; Dr. Ayesha Imran; Dr. Monika Pathania; Dr. Gowhar Wani; Dr. Anumodhan Gupta (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: As there is paucity of data on Scrub typhus from Garhwal belt. So, to bridge this gap we conducted this study and tried to bring awareness about Scrub typhus.Methods: This is a descriptive study of 40 patients who were ELISA positive for Scrub typhus. A detailedhistory, demographic details, clinical features, complications, routine laboratory parameters and their relation with and without eschar was noted.Results: On analysis of demographic details, majority of scrub typhus patients belonged to Hilly district, Rudraprayag of Garhwal region. Common signs included fever (100%), lymphadenopathy and splenomegaly (70%), hepatomegaly (55%), rash (37%), eschar (35%), meningitis (20%), hepatitis and epistaxis (5%), pleural effusion, sub-conjunctival hemorrhage and ARDS (2.5%). Presence of eschar was strongly associated with abdominal pain, facial edema, meningitis and ARDS.Conclusion: Early diagnosis with high index of suspicion and timely treatment in children from hilly area with acute febrile illness decreases the mortality and leads to better prognosis.